Beacons positioning detection, a novel approach - Morgado, Francisco (2019)
Recent Bluetooth Low Energy (BLE) beacons provide new opportunities to explore positioning. Beacon positioning determination using current approaches is supported by pre-calculated formulas, for generic beacons, whereas the position can be accurately estimated with a low error up to a small distance; or based on fingerprinting the signal for the given space. In both cases, the accuracy variate depending on hardware specifications and other conditions such as beacon brand, wrap material, temperature, wind, location, surrounding interference, battery strength, among others. This paper introduces a method for beacon-based positioning, based on signal strength measurements at key distances for each beacon. This method allows for different beacon types, brands, and conditions. Depending on each situation (i.e., hardware and location) it is possible to adapt the distance measuring curve to minimize errors and support higher distances, while at the same time keeping good precision. Moreover, this paper also presents a comparison with traditional positioning method, using formulas for distance estimation, and then position triangulation. Performed tests took place at the library of the campus of the Polytechnic Institute of Viseu. Experimental results show that the proposed position technique has 13.2% better precision than triangulation, for distances up to 10 meters.